Policy Implementation Analysis on Exclusive Breastfeeding in Working Area of Cicalengka Community Health Center in Bandung Regency West Java - Mardhatillah, Innana; Ilyas, Yaslis (UI Scholars Hub, 2018)
Data and information on the health profile of Indonesia in 2016 showed only 29.5% of infants receive exclusive breastfeeding until 6 months, the low level of exclusive breastfeeding made the government issue a regulation on exclusive breastfeeding in Government Regulation Number 33 of 2012. The study aimed to analyze the policy implementation of exclusive breastfeeding at Cicalengka Community Health Center. The study used qualitative analysis with in-depth interview method, focus group discussion and literature study. The result of this study shows that breastfeeding policy implementation in health centers is not optimal, as seen from the low coverage of exclusive breastfeeding. Socialization of the policy has not been done as a whole, the time and task division is unclear and has no special budget and the standard operating procedures is not really used in carrying out the policy. Communication is the most influential factor in the implementation of the policy. There is no support and commitment from all employees in the implementation of exclusive breastfeeding policy. The suggestion is to consistently socialize to employees and the public, carry out supervision in an effort to secure the policy, run the Standard Operating Procedure (SOP), allocate budget activities in 2018, create a memorandum of understanding with other agencies, and Self-assessment and program evaluation absolutely must do continuously.